Architecture form, space, & order - Ching, Francis D. K. 1943- (Wiley, 2015)
"This is an introduction to the basic vocabulary of architectural design, updated with new information on emerging trends and recent developments. The book is a visual reference that helps both students and professionals understand the vocabulary of architectural design by examining how space and form are ordered in the environment"--Provided by publisher